1999
DOI: 10.1063/1.369677
|View full text |Cite
|
Sign up to set email alerts
|

Low dielectric constant films prepared by plasma-enhanced chemical vapor deposition from tetramethylsilane

Abstract: Dielectric films have been prepared by radio-frequency plasma-enhanced chemical vapor deposition from mixtures of tetramethylsilane with oxygen. The films have been characterized as-deposited and after annealing at 400 °C to determine the thermal stability of their properties. Rutherford backscattering and forward recoil elastic scattering have been used for determination of the composition of the films. Optical properties were characterized by Fourier transform infrared spectroscopy and measurements of the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 7 publications
2
127
1
Order By: Relevance
“…[3][4][5][6][7] The synthesis of a fluorocarbon-organosilicon copolymer offers the opportunity to incorporate the useful characteristics of both fluorocarbon and organosilicon polymers into a single thin film. Fluorocarbon-organosilicon copolymers are currently under investigation as candidate materials for biopassivation coatings on neurological implants.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7] The synthesis of a fluorocarbon-organosilicon copolymer offers the opportunity to incorporate the useful characteristics of both fluorocarbon and organosilicon polymers into a single thin film. Fluorocarbon-organosilicon copolymers are currently under investigation as candidate materials for biopassivation coatings on neurological implants.…”
Section: Introductionmentioning
confidence: 99%
“…This results contrasts with those reported by other authors showing the formation of SiO 2 thin films by using TMS in plasma microwave reactors with downstream configurations. 13,24 Jauberteau et al 25 have reported that an afterglow Ar plasma may yield a large fragmentation of the TMS molecule, mainly via SiuC bond breaking. This process principally generates Si(CH 3 ) fragments.…”
Section: Plasma-enhanced Chemical Vapor Deposition Thin-film Formamentioning
confidence: 99%
“…11 Other authors have also shown that by using TMSϩO 2 , it is possible to deposit hydrophobic SiO x thin films in a corona discharge plasma at atmospheric pressure. 6 In addition, since TMS and TMSCl do not contain oxygen, it is possible to deposit SiC and polymeric SiC x H y thin films 12,13 without adding to the plasma CH 4 or other hydrocarbons, as has to be done when using SiH 4 . However, in contrast with the ample literature existing about the use of SiH 4 , TEOS, or HDMSO, much less is known about the use of TMS or TMSCl.…”
Section: Introductionmentioning
confidence: 99%
“…117 Carbon-doped SiO 2 ͑SiOCH͒ films have k values below 2.8; the difficulty is controllably ''balancing'' the carbon content, OH content, and porosity. 118,119 Extensive reviews of PACVD are available. 117,120,121 Currently, plasma-assisted etching and deposition for microelectronic device and IC fabrication are reasonably mature technologies.…”
Section: Plasma-assisted Deposition (Pacvd)mentioning
confidence: 99%